गोसोनि बारहुंखा - Nandeswar Boro (Bodo Publication Board Bodo Sahitya Sabha, 1993)
Gwswni Barhungkha is a collection of poems in Bodo language.
Gwswni Barhungkha
Keywords: Bodo; Literature; Bodo; Bodo